The Effect of Different Rice Straw and Concentrate Content of The Ration on Hemicellulase Activity in The Rumen Fluid of Carabao, Cattle, Goat and Sheep - Z. Bachrudin; L. M. Yusiati; R. Utomo; W. Asmara; E. W. Cahyono (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy